Development of STEAM-Based Belawa Tortoise Conservation E-Supplement to Improve Higher Order Thinking Skills in High School Ecosystem Material - Mudaningrat, Ajeng; Marianti, Aditya; Ellianawati, Ellianawati; Parmin, Parmin; Widiyatmoko, Arif (Unnes Science Education Journal, 2024)
Using local potential as teaching materials is an effort to meet the learning outcomes of class X biology subjects. This research aims to develop a STEAM-based Belawa Tortoise conservation e-supplement to improve higher-order thinking skills in high school ecosystem materials. This research is a Research and Development research using the ADDIE model The ADDIE development model is composed of the analyze, design, development, implementation and evaluation stages, but is limited to the implementation stage, namely small-scale tests. The small-scale test was conducted on 10 students of grade XI MAN 3 Buntet Pesantren Cirebon. The results showed that STEAM-based Belawa Tortoise conservation e-supplements have characteristics that there are local wisdom offerings with conservation content, virtual tours equipped with representative pictures and videos, STEAM-based student activities. E-supplements are valid and feasible to use based on the assessment of material experts and media experts with small-scale test results having an average of 94.6 with excellent criteria and unrevised qualifications. Based on the research, it can be concluded that the STEAM-based Belawa Tortoise conservation e-supplement is declared feasible, potentially to improve the higher-order thinking skills of high school learners.